Joseph Roth's Feuilleton Journalism as Social History in Vienna, 1919–20. (20th April 2017) - Holmes, Deborah
Abstract : From April 1919to April 1920, twenty-four-year-old Joseph Roth worked full time as a reporter on the newly founded Viennese daily Der Neue Tag [The new day]. It was his first regular job and, although he was later to become one of the best-paid journalists of the Weimar Republic, it was also the only one he would ever hold on a fixed contract. In spring 1919, Roth had recently returned from eastern Galicia, the place of his origins, where he had also been stationed during the war, first in the infantry, then as an army press officer. His position as a Heimkehrer in Vienna after the war was precarious for a number of reasons. Paid work was scarce in the impoverished city, and Roth had not finished—indeed, would never finish—his degree. More important, although he had already been resident in Vienna as a student before the outbreak of hostilities, the "Ostjude" Roth, like so many others, had no valid papers and no right to remain in the former imperial capital. Political parties across the spectrum were agitating for the largely Jewish refugees from the former eastern provinces of the fallen Habsburg empire to be sent "home"—even by force, if necessary. Roth's position at Der Neue Tag was therefore not only an important apprenticeship for his high-profile career in journalism—which in turn laid the foundations for his oeuvre as a novelist—but also constituted a vital existential anchor. Given their historical and biographical context, it seems surprising that the texts he produced for the new newspaper—two or three a week throughout this pivotal period in Vienna's transition from self-assured imperial capital to beleaguered Social Democratic outpost—have received comparatively little attention in Roth scholarship. This is in part a result of the acknowledged bias in research on German-language culture and literature during this era toward the Weimar Republic, in particular Berlin, and away from First Republic Austria: similar texts produced slightly later by Roth in and on the German capital are often studied and seem to have eclipsed the earlier Viennese texts. This article seeks to redress the balance within Roth scholarship while also suggesting what Roth's work for Der Neue Tag can contribute to our sociohistorical understanding of the period, despite or perhaps because of the literary techniques it uses.